Hour of the wolf. Vol.1 - London, Mark (Graphic novelist) (Mad Cave Studios, 2025)
When Owen Blackwood is called across time to a seemingly normal home to destroy a haunted painting, it didn't feel like anything out of the ordinary to this agent of Wolvenheart. Upon arrival, however, Owen finds himself trapped in the very painting he was called to destroy. With only a one hour window of time in which to operate, will Owen be able to save the family from certain death and destroy the painting? Or will he get lost in time and become a cross-dimensional walking ghost?